Molecular characteristics of coals at different coal seams in the same mine obtained by high performance separation methods. (15th August 2022) - Xu, Jian-Fang; Wang, Fei; Fan, Xing; Muhammad, Turghun; Kuznetsov, Peter N.; Ma, Ya-Ya
Highlights: Prep-HPLC was applied to separate and enrich components in coal extracts. Much more compounds were detected in enriched fractions of soft and hard coals. Molecular characteristics of coals at different coal seams in the same mine were studied. Abstract: Two coal samples in the same mine but different coal seams, soft coal and hard coal, were subjected to a parallel thermal dissolution process using two organic solvents to obtain four soluble portions (SPs). A preparative high performance liquid chromatography (prep-HPLC) with a fraction collector was introduced to obtain twenty-eight fractions from the SPs. Both gas chromatograph/mass spectrometry (GC/MS) and Orbitrap-MS with a collision cell were employed to elucidate the molecular structure of soluble species. Some heavy aromatic compounds in SPs not identified by GC/MS were detected in fractions, indicating that the off-line prep-HPLC is of perfect separation and enrichment ability, and can improve the reliability of analytical data. In addition, to preferably elucidate the difference in composition of compounds between the two coals, the possible fragmentation pathways in the collision cell were proposed. Such accurate identification will provide theoretical guidance for the efficient utilization of coals in the same mine but different coal seams, and the safety guidance to avoid mine accidents generated by the inconsistence in coal seams.